THE AMPHIBIAN FAUNA IN THE VILLAVICENCIO REGION OF EASTERN COLOMBIA - LYNCH JOHN D. (Caldasia)
The Villavicencio Region, at the base of the eastern mountain range, harbors an amphibian fauna consisting of three caecilians, 45 frogs, and one salamander. This fauna includes 16 abundant species of frogs and toads that occupy open habitats and which do not invade forested areas of these lowlands. An additional 24 species require moist conditions and occur principally in areas supporting forests. Seven other species are species of the Andean slopes that have their lowest records in the lowlands. This local fauna is enriched in treefrogs and impoverished in terms of centrolenids and leptodactylids relative to the diversities of various amphibian groups in the country as a whole.